User responses to a smart charging system in Germany: Battery electric vehicle driver motivation, attitudes and acceptance - Schmalfuß, Franziska; Mair, Claudia; Döbelt, Susen; Kämpfe, Bettina; Wüstemann, Ramona; Krems, Josef F.; Keinath, Andreas (Energy research & social science, 2015)
Smart charging systems for battery electric vehicles (BEVs) are one promising smart grid technology that has the potential to help balance energy supply and demand. In the present study, we aimed to investigate users' real-life experiences with a smart charging system and their evaluation of it. In a 5-month field trial, 10 BEV drivers compared conventional BEV charging with smart charging. Via smartphone application, users could modify settings which determined the charging process (e.g., departure times). Before and after experiencing the prototype system, users' motivation, attitudes, willingness to use smart charging and charging behavior were assessed via interviews and questionnaires. Furthermore, participants reported how they experienced and integrated the smart charging system. Results showed that users were motivated and positive about the system at both points of data collection. On average, users agreed that the system is suitable for daily life, reliable and trustworthy. They were willing to use smart charging before and after testing it, but some participants stated that reliability of the system should be improved. In sum, results indicate that a smart charging system like the one implemented in this study is assimilable in everyday life and provide valuable indications for further development of smart charging systems.